(untitled) (Eastern Journal of Medical Sciences, 2017)
Introduction: Esophageal carcinoma is the eight most common cancer in the world. The management of locally advancedcarcinoma esophagus is mainly palliative with chemoradiotherapy. The outcome data of such a modality along with oralmetronomic chemotherapy after treatment completion are sparse. Here, we present the outcomes of treatment of locally advancedunresectable esophageal cancer after palliative chemoradiotherapy and oral metronomic therapy from a rural setting in India.Methods: Retrospective analysis of all patients of locally advanced unresectable nonmetastatic esophageal carcinoma treatedwith short course of induction chemotherapy followed by radiotherapy/chemoradiotherapy and oral metronomic chemotherapywas performed. The primary aim was estimation of progression free-survival (PFS) and overall survival (OS). Results: A total of45 patients were analyzed. Mean age was 55 years (30-85 years). A total of 32 patients had tumors in upper and middle esophagus,with the most common histology being squamous cell carcinoma (N-41). The estimated 2 year PFS is 47.2% and the estimated2 years OS is 57.8%. Conclusion: Combined modality therapy with adjuvant oral metronomic therapy shows promising results inthe management and should be the basis of further trials.